PERANAN FASHION DAN PAKAIAN SEBAGAI KOMUNIKASI IDENTITAS SOSIAL - Netty Lisdiantini; Subiyantoro; Yosi Afandi (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2019)
As one of the clearest markers of many outward appearance markers, clothing is a distinctive individual and group identity. Therefore, even though being worn in a single organization, the symbol of uniform can have its own identity and tradition. Fashion and clothing are ways that individuals use to determine themselves as individuals and express some of their uniqueness. As a form of individualistic expression, there are values in fashion that are promoted or communicated through what is displayed. Relating this concept to dress policies for students of the Madiun State Polytechnic Business Administration Study Program on certain days. In terms of context, the evaluation results using the CIPP evaluation model (context, input, process, product) shows that, the implementation of this policy supports a character that is more disciplined, obedient and orderly in regulations, creates authority through habituation and can reduce economic inequality and establish a sense of belonging towards the Study Program institutions and a sense of unity, as an identity or differentiation with other Study Program students. With regard to input, although there are various reactions to the implementation of the policy, there is no direct rejection. From the prospective of process, the means used are announcements posted on the Announcement Board of the Department and policy writing in the Guidebook. Whereas in terms of product, the changes that occur after students wear uniforms are to be more orderly, more disciplined, more controlled in acting, as well as feeling more authoritative, and can be emulated